Conjugated Polymers: Linking Group Influences Charge Separation and Recombination in All‐Conjugated Block Copolymer Photovoltaics (Adv. Funct. Mater. 35/2015). (15th September 2015) - Mok, Jorge W.; Lin, Yen‐Hao; Yager, Kevin G.; Mohite, Aditya D.; Nie, Wanyi; Darling, Seth B.; Lee, Youngmin; Gomez, Enrique; Gosztola, David; Schaller, Richard D.; Verduzco, Rafael
Abstract : Fully conjugated block copolymers with donor and acceptor polymer blocks can function as the active layer of an organic photo‐voltaic device. On page 5578, R. Verduzco and co‐workers demonstrate that the linking group at the donor‐acceptor junction is critical for charge separation. Proper design of the linking group is essential for producing viable block copolymer photovoltaic devices.